Signaling Overview of Plant Somatic Embryogenesis - Méndez-Hernández, Hugo A.; Ledezma-Rodríguez, Maharshi; Avilez-Montalvo, Randy N.; Juárez-Gómez, Yary L.; Skeete, Analesa; Avilez-Montalvo, Johny; De-la-Peña, Clelia; Loyola-Vargas, Víctor M. (Frontiers in Plant Science, 2019)
Somatic embryogenesis (SE) is a means by which plants can regenerate bipolar structures from a somatic cell. During the process of cell differentiation, the explant responds to endogenous stimuli, which trigger the induction of a signaling response and, consequently, modify the gene program of the cell. SE is probably the most studied plant regeneration model, but to date it is the least understood due to the unclear mechanisms that occur at a cellular level. In this review, the authors seek to emphasize the importance of signaling on plant SE, highlighting the interactions between the different plant growth regulators, mainly auxins, cytokinins, ethylene and abscisic acid, during the induction of SE. The role of signaling is examined from the start of cell differentiation through the early steps on the embryogenic pathway, as well as its relation to a plant’s tolerance of different types of stress. Furthermore, the role of genes encoded to transcription factors during the embryogenic process such as the LEAFY COTYLEDON (LEC), WUSCHEL (WUS), BABY BOOM (BBM) and CLAVATA (CLV) genes, Arabinogalactan-proteins (AGPs), APETALA 2 (AP2) and epigenetic factors is discussed.